Близнецы. Завещание сына: [роман] / Андрей Анисимов - Анисимов Андрей Юрьевич (Детектив, 2005)
Экземпляры: ф.2 (2008) / Инвентарный номер: 51915 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4